2022
DOI: 10.1038/s42004-022-00721-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the use of absolute binding free energy in the fragment optimisation process

Abstract: Key to the fragment optimisation process within drug design is the need to accurately capture the changes in affinity that are associated with a given set of chemical modifications. Due to the weakly binding nature of fragments, this has proven to be a challenging task, despite recent advancements in leveraging experimental and computational methods. In this work, we evaluate the use of Absolute Binding Free Energy (ABFE) calculations in guiding fragment optimisation decisions, retrospectively calculating bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 114 publications
5
57
2
Order By: Relevance
“…It is possible that the restraints between the phenol and this Asn, which quickly forms a H-bond to water upon its entry to the binding site, created particularly high barriers to the entry of water, giving rise to systematic error. Regardless, the difference observed suggests that the approach of running independent replicate simulations with different restraints, as taken by Alibay et al, is sensible.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…It is possible that the restraints between the phenol and this Asn, which quickly forms a H-bond to water upon its entry to the binding site, created particularly high barriers to the entry of water, giving rise to systematic error. Regardless, the difference observed suggests that the approach of running independent replicate simulations with different restraints, as taken by Alibay et al, is sensible.…”
Section: Resultsmentioning
confidence: 97%
“…For each pair, adjacent heavy atoms were selected to complete the sets of Boresch anchor points. These sets were ordered by increasing total variance of the Boresch DoF, as done by Alibay, , and sets of anchor points were discarded if the average values of θ A or θ B were below 30 or above 150 degrees. The equilibrium values for all restraints were taken to be their average values during the unrestrained simulation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 853 simulation cases from 34 different research groups (from 47 papers, i.e. , refs , ) and from distinct schools of thought ( i.e. , routes, force fields, etc .)…”
Section: Results and Discussionmentioning
confidence: 99%
“…Since ligands are treated individually, they do not need to share a common scaffold and can be structurally diverse. This means that ABFE could be used even in early project stages where structurally diverse ligands are common and has been proposed to serve as a final scoring stage in virtual high throughput screening before selecting molecules for experimental testing. , Recent studies showed that ABFE can achieve a good correlation between predicted and experimental binding free energies across different systems and can even be used to estimate binding to different proteins, allowing computation of the selectivity of ligands for a particular target …”
Section: Introductionmentioning
confidence: 99%